Content validation of the nursing intervention Dialysis Access Maintenance - Letícia Mattos Gonçalves; Silvia Maria de Sá Basílio Lins; Priscilla Alfradique de Souza; Joyce Martins Arimatéa Branco Tavares; Bruna Maiara Ferreira Barreto Pires; Luciana Guimarães Assad (Universidade Federal do Ceará, 2021)
Objective: to validate the content of the Dialysis Access Maintenance intervention. Methods: methodological validation study, composed of 28 participants who analyzed each activity of the intervention through the Likert scale, considering the importance and objectivity, which provided the calculation of the index of validity of content and frequency to assess the realization of the activities. Results: the 11 intervention activities were validated. Of these, seven obtained a content validity index ≥ 0.8 and four, > 0.5 and < 0.8. In the qualitative part, three categories emerged: 1) Positive reinforcement of the Nursing Interventions Classification activity; 2) Contribution to improve the Nursing Interventions Classification activity; and 3) Disagreement regarding the activity proposed by the Nursing Interventions Classification. Conclusion: all activities were considered important and objective, validating the intervention.